Identifying Tarbiyah, Ta'lim, and Ta'dib as a Grand Design for Character Education for the Younger Generation - Endan Hamdan Ridwan (Insitut Muslim Cendekia, 2025)
This study is motivated by the importance of the concept of Islamic education in the era of globalization and the young generation, particularly in shaping holistic character. In this context, Islamic education rests upon three core pillars: tarbiyah (nurturing), ta’lim (instruction), and ta’dib (inculcation of proper conduct), each of which carries its own meaning and function, such as educating, maintaining, and guiding. These three concepts are highly relevant to restoring and reinforcing moral and ethical values that are gradually fading among the young generation . The purpose of this research is to establish tarbiyah, ta’lim, and ta’dib as the grand design of character education for young generation so that they may behave with courtesy, ethics, and noble morals within the framework of Islamic education, and become well-prepared to face future challenges. The study employs a qualitative method with a descriptive-narrative approach. The main focus lies in character formation and courteous behavior, encompassing stages of data collection, analysis, presentation, and conclusion. The findings indicate that although tarbiyah, ta’lim, and ta’dib possess distinct meanings, all three share a common goal in shaping a holistic form of Islamic education.